An evaluation of the Arabian Sea Mini Warm Pool's advancement during its mature phase using a coupled atmosphere–ocean numerical model - S. P. Lahiri; K. R. Prakash; K. R. Prakash; V. Pant (Ocean Science)
A coupled atmosphere–ocean numerical model is used to examine the relative contributions of atmospheric and oceanic processes in developing the Arabian Sea Mini Warm Pool (MWP). The model simulations were performed for three independent years, 2013, 2016, and 2018, through April–June, and the results were compared against observations. The model-simulated sea surface temperature (SST) and sea surface salinity (SSS) bias were less than 1.75 °C and 1 psu, respectively; this bias was minimal in the MWP region. Moreover, the model simulated results effectively represented the presence of the MWP across the three different years. The mixed-layer heat budget analysis indicated that the net surface heat flux raised the mixed-layer temperature tendency of the MWP by a maximum of 0.1 °C d−1 during its development phase. The vertical processes exerted a cooling impact on the temperature tendency throughout May and June with a maximum of −0.08 °C d−1. Nonetheless, the decrease of net surface heat flux emerged as the dominant factor for the dissipation of the MWP. Further, four sensitivity numerical experiments were performed to investigate the comparative consequences of the ocean and atmosphere on the advancement of the MWP. The sensitivity experiments indicated that pre-April ocean conditions in years with a strong MWP resulted in a 136 % increase in MWP intensity in years when MWP SST was close to the climatology, which shows the primary role of oceanic preconditioning in determining MWP strength during strong-MWP years. Once the oceanic preconditions are met, the atmospheric conditions of weak-MWP years lead to an 82 % reduction in MWP intensity relative to normal years, highlighting the detrimental impact of atmospheric forcing under such circumstances. Atmospheric conditions, particularly wind, are critical in influencing the spatial evolution and dissipation of the MWP in the southeastern Arabian Sea (SEAS). A wind shadow zone, characterized by less production of turbulent kinetic energy that does not exist during weak-MWP years, facilitates the spatial expansion of the MWP in SEAS during moderate to strong-MWP years.